Coral Reef Water Microbial Communities of Jardines de la Reina, Cuba - Manon Denux; Maickel Armenteros; Laura Weber; Carolyn A. Miller; Kinga Sántha; Amy Apprill (Microorganisms)
Globally, coral reef ecosystems are undergoing significant change related to climate change and anthropogenic activities. Yet, the Cuban archipelago of Jardines de la Reina (JR) has experienced fewer stressors due to its geographical remoteness and high level of conservation. This study examines the surface and benthic reef water microbial communities associated with 32 reef sites along the JR archipelago and explores the relationship between the community composition of reef microorganisms examined using bacterial and archaeal small subunit ribosomal RNA gene (16S rRNA gene) sequencing compared to geographic, conservation/protection level, environmental, physicochemical, and reef benthic and pelagic community features. Reef nutrient concentrations were low and microbial communities dominated by picocyanobacteria and SAR11 and SAR86 clade bacteria, characteristic of an oligotrophic system. Reef water microbial community alpha and beta diversity both varied throughout the archipelago and were strongly related to geography. Three sites in the western archipelago showed unique microbial communities, which may be related to the hydrogeography and influences of the channels linking the Ana Maria gulf with the Caribbean Sea. Overall, this work provides the first extensive description of the reef microbial ecology of the Caribbean’s ‘Crown Jewel’ reef system and a framework to evaluate the influence of ongoing stressors on the reef microorganisms.